Effect of Different Times of Intraperitoneal Injections of Human Bone Marrow Mesenchymal Stem Cell Conditioned Medium on Gentamicin-Induced Acute Kidney Injury - Abedi, Azam; Azarnia, Mahnaz; Jamali zahvarehy, Mansor; foroutan, Tahereh; Golestani, Sara (Urology Journal, 2016)
Purpose: This study examined the effect of mesenchymal stem cells’ conditioned media on the severity of acute kidney injury. Materials and Methods: Acute kidney injury was induced in male rats with 100 mg/kg of gentamicin for six consecutive days intraperitoneally. After inducing the standard model of acute kidney injury, the conditioned medium of 5 × 106 cells was calculated for each kilogram of body weight of the rats. Then, it was injected in three different injection patterns other than the baseline injection of gentamicin. The rats were randomly divided into four groups: control group (n = 18) that did not receive any treatment, gentamicin group (n = 18) that received gentamicin at a dosage of 100 mg/kg for six consecutive days intraperitoneally, sham group (n = 54) that received gentamicin for six consecutive days, and an experimental group (n = 54) that received gentamicin for six consecutive days. Serum biochemical analysis and histological changes were studied and analyzed in all groups. Results: Although human mesenchymal stem cells’ conditioned media did not improve serum and tissue markers in the treatment groups, a relative improvement was observed in some indicators of tissue damage. Conclusion: Secretory factors of human mesenchymal stem cells can be partly protective against gentamicin-induced nephrotoxicity.